Study on Rheological Thermo-visco-elasticity with Two-temperature Effect - M. K. Mondal; M. B. Bera (Current Overview on Science and Technology Research Vol. 9, 2022)
The aim of this article is to investigate the two-temperature effect over the viscoelastic material, which is used in our day to day life as well as in the industrial field. The rheological effects of thermo-visco-elastic materials are important in several engineering aspects as well as in the thermal industry. Despite the fact that several works are related to rheology, the combination of rheology and two-temperature is significant. The two-temperature thermo-visco-elastic problem of an isotropic material in two-dimensional systems is the subject of this research. Here, the volume and density rheological characteristics of the substance are described. In the generalised heat conduction equation, three different theories-Lord-Shulman (LS), Green-Lindsay (GL), and classical coupled theory (CD)-have been applied. By using normal mode analysis, the pertinent expressions are resolved. A homogenous flat plate of magnesium crystal-like material with appropriate boundary conditions is taken into account for numerical support. In order to estimate the impact of the temperature mismatch between the various theories, several comparisons in figures have been done.